The Greek versions of the TeamSTEPPS teamwork perceptions questionnaire and Minnesota satisfaction questionnaire "short form" - Lakatamitou, Ioanna; Lambrinou, Ekaterini; Kyriakou, Martha; Paikousis, Lefkios; Middleton, Nicos (My University, 2020)
Teamwork and job satisfaction are important among the multidisciplinary team who care patients with chronic illnesses such as heart failure (HF) patients. TeamSTEPPS teamwork perceptions questionnaire (T-TPQ) and Minnesota Satisfaction Questionnaire "short form" (MSQ-short) are both self-report questionnaires which examine multiple dimensions of perceptions of teamwork and job satisfaction within healthcare settings, respectively. The aim of the study was to examine the psychometric properties of the Greek versions of the TeamSTEPPS Teamwork perceptions questionnaire (Gr-T-TPQ) and Minnesota Satisfaction Questionnaire "short form" (Gr-MSQ-short).
Keywords: Gr-MSQ-short; Gr-T-TPQ; Job satisfaction; Teamwork; Tools; Validation